Gender and difference in the Middle Ages - Farmer, Sharon A.; Pasternack, Carol Braun (Medieval cultures ;, 2003)
Nothing less than a rethinking of what we mean when we talk about "men" and "women" of the medieval period, this volume demonstrates how the idea of gender -- in the Middle Ages no less than now -- intersected in subtle and complex ways with other categories of difference. Responding to the insights of postcolonial and feminist theory, the authors show that medieval identities emerged through shifting paradigms -- that fluidity, conflict, and contingency characterized not only gender, but also sexuality, social status, and religion. This view emerges through essays that delve into a wide variety of cultures and draw on a broad range of disciplinary and theoretical approaches. Scholars in the fields of history as well as literary and religious studies consider gendered hierarchies in western Christian, Jewish, Byzantine, and Islamic areas of the medieval world.